Globalisasi Mengubah Konsep Negara, Teritori, Kedaulatan : Integrasi ALBA sebagai Sovereignty Counter-Balance - Wahyuni Andike; Siti R Susanto (Jayapangus Press, 2022)
Globalization as a dynamic process has contributed to change and downgrade the power of. Most state experience various development regarding cross-border interaction, such as in economy, politics, and culture. Although the Westphalia Treaty of 1648 was a turning point where loyalty of people must be given to the state, yet it is shown that the power of state does no longer exist as the only political power. Venezuela’s Populist economic policies under Nicolas Maduro considered as failed-state management which lead the country reaching equitable welfare. Regarding Venezuela from the start in the ALBA (the Bolivarian Alliance for the peoples of our America), it has been able to help a little compilation of this country to improve the crisis, asking that the ALBA here try to be seen as